Research on android user privacy permission analysis and protection mechanism under big data environment - Liu Mei; Wang Qun (MATEC Web of Conferences, 2024)
With the rapid development of big data technology, the issue of user privacy security on the Android platform is becoming increasingly prominent. This paper aims to conduct an in-depth analysis of the privacy permissions of Android users under the big data environment and explore effective protection mechanisms. Through research on permission management, application behavior, and user privacy leakage pathways in the Android system, this paper proposes a comprehensive privacy protection strategy to enhance the privacy security level of Android users in the big data environment.